Predictors of Full Recovery in Patients with Early-Stage Schizophrenia Spectrum Disorders - Muhammad Fahim Qasim, Muhammad Asif Kamal, Shafqat Huma, Fatima Aamir Khan, Nadia Naveen (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: In the last 20 years, there has been an increase in research on self-stigma among persons with severe mental illness. Objectives: The main objective of the study is to find the predictors of full recovery in patients with early-stage schizophrenia spectrum disorders. Material and methods: This cross-sectional study was conducted in Wah medical college / POF hospital Wah Cantt during 2021-2022. Data was collected with the permission of ethical committee of hospital. At the time of analysis, 57 patients with early-stage psychosis had enrolled. Early-stage was defined as the duration of adequate antipsychotic treatment of more than 4 weeks but less than or equal to 2 years. We restricted analysis to individuals diagnosed as having SSD (schizophrenia [SZ] and schizophreniform disorder [SZFD]) and PNOS. Results: Data were collected from 34 patients. Mean age of the patients was 28.4 ± 8.5 years. There were 8 (39.0) males and 26 (61.0) female patients. 2.37% patients were unemployed. There were 28 (94.9) patients with family history of diseases. A comparison of the demographic and clinical characteristics of subjects being followed up versus those that had dropped out revealed no significant differences, with the exception of education and intensity of suicidal ideation. Practical implication: This study will help us to find the predictors of full recovery in patients with early-stage schizophrenia. Conclusion: It is concluded that significant predictors for full recovery were duration of untreated psychosis (DUP), family intimacy and physical activity. We observed similar or better results on remission, recovery, and relapse rates compared to other previous studies. Keywords: Early, Relapse, Compared, Recovery, DUP, Physical, Significant